Análisis financiero de las cuentas por cobrar en el cuerpo de bomberos municipal de Puebloviejo en el período 2020-2021. - Santana Muñoz, Jackson Joel (2022)
The subject of this case study is financiar analysis of the municipal fire department of Puebloviejo in the period 2020-2021 the Company is dedicated to defend the citizens of the cantón of Puebloviejo to fight fires, road accidents and especially in times of winters when floods are caused. In the development of the research, the subline of financial management, tax and social commitment was used and the technique is the collection of information. The case study is carried out with the descriptive methodology by which it will be possible to analyze investigate, verify and check on the facts that have been made in the Company, with the intervention of the financial departments of the Company provided us with the necessary documents to learn more about the Company and diagnose the problems that efficiency of its operations in which we provided the trial balance, statement of financial position, statement of Budget execution, the objective is to recognize and analyze the financial and economic situation of the Company with the various procedures to verify the Company is in an optimal way to face an economic emergency that requires and investment, remembering that the fire department of the cantón of Puebloviejo needs to have equipment such as tolos and adequate clothing to prevent and respond to and emergency that the citizens of the cantón of Puebloviejo need.